Density functional theory studies of O2, H2O, OH- and xanthates adsorption on platinum antimony (PtSb2) surfaces - Mangoejane, Samuel Seshupo (My University, 2020)
The effects of O2, H2O and OH− and collectors are the major factors that determine the flotability behaviour of minerals. In particular, the influence of the chain length variation on xanthate collectors gives rise to increased recovery rates, and are still the most versatile collector for most minerals. This study explores the bonding behaviour, adsorption energies and electronic properties directly related to the reactivity of O2, H2O and OH−, ethyl xanthates (EX), normal propyl-xanthate (nPX), normal-butyl-xanthate (nBX–) and amyl-xanthate (AX) with the platinum antimony mineral surfaces: (100), (110) and (111) surfaces. We employed the ab-initio quantum mechanical density functional theory to investigate their adsorption and their electronic properties. In order to attain precise calculations, the cut-off energy of 500 eV was used for the bulk PtSb2, which was also transferred to the surfaces. To obtain accurate results the k point used for both the bulk and surfaces were 6x6x6 and 4x4x1, respectively. The bulk relaxation was found to give final lattice parameter of 6.531 Å. The DOS (Density Of States) indicated that both bulk and surfaces of PtSb2 had a metallic character, thereby indicating semiconducting behaviour. In cleaving the surfaces, all possible terminations were considered and the slab thickness was varied to obtain the desired stable surfaces. Their relaxed surface energies were 0.807 J.m-2, 1.077 J.m-2 and 1.074 J.m-2 for the (100), (111) and (110), respectively. These indicated that the (100) surface was the most stable and dominant plane for the platinum antimony. This fact is also observed in other minerals in general that low-index surfaces with lower surface energies indicates structural stability. The DOS showed stability with the EF (Fermi level/ Fermi energy) falling deep into the pseudo gap for all surface. The valence electrons on the surface were 5d96s1 for Pt and 5s25p3 for Sb as depicted from the Mulliken population charges and these electrons were actively involved in the hybridisation. The oxidation showed that the oxygen molecules preferred interacting with the Sb atoms than the Pt atoms for all surfaces. For the (100) surface we found that the Pt-O2peroxide adsorption site gave the strongest adsorption, while for the (110) surface we noted that the Sb2-O-O-Sb3 bridging gave the most exothermic adsorption. The case of the (111) surface showed the Sb2-O-O-Sb2 bridging to give the strongest exothermic adsorption, which dissociated and resulted in atomic bonding. Their atomic charges indicated that the oxygen molecules gain charges from the Pt and Sb atoms. In all cases, PtSb2 Bulk PtSb2 (100), (110) and (111) surfaces O2, H2O, OH-and Xanthates adsorptions the O2 interacting with Sb gained more charges, thus showing preferential adsorption to the Sb atoms. In addition, the Sb/Pt-bonded oxygens were more negative than the terminal or end-bonded oxygen atom for superoxide modes. These suggested that the 2p-orbital spin-down unoccupied orbital (LUMO) of O2 is fully occupied. The case of H2O molecules adsorptions on the three PtSb2 mineral surfaces indicated that the H2O adsorbed through van der Waals forces, in particular for multi adsorptions by physisorption process for the (100) and the (110) surfaces. However, on the (111) surface we observed chemisorption adsorption. For the (100) surface we found that the H2O-Pt was exothermic, while the H2O-Sb was endothermic and only showed exothermic from 5/8-8/8 H2O/Sb. The case of the (110) surface showed stronger adsorption of H2O on Pt than on Sb atoms, with a weaker adsorption on Sb2 atoms, while the adsorption on the (111) surface was stronger on Sb3 and weaker on Sb2 atoms. The full-coverage for the (110) surface gave –35.00 kJ/mol per H2O molecule, which is similar to the full coverage on the (100) surface (–38.19 kJ/mol per H2O molecule). Furthermore, the full monolayer adsorption on Sb2 and Sb3 for the (111) surface gave much stronger adsorption (–55.54 kJ/mol per H2O). In addition, the full-coverage on the (111) surface (i.e. on Pt1 and all Sb atoms) gave adsorption energy of –54.95 kJ/mol per H2O molecule. The adsorption of hydroxide on the surfaces showed stronger affinity than the water molecules. This suggested that they will bind preferentially over the water molecules. We also found that the OH–preferred the Sb atoms on the (100) surface, with a greater adsorption energy of –576.65 kJ/mol per OH– molecule for full-surface coverage. The (110) surface adsorption energy on full-surface coverage was –541.98 kJ/mol per OH molecule. The (111) surface full-coverage yielded adsorption energy of –579.53 kJ/mol per OH– molecule. The atomic charges related to both hydration and hydroxide adsorption showed charge depletion on both Pt/Sb and O atoms of the H2O and OH–. This suggested that there is a charge transfer into other regions within the orbitals. The adsorption of collectors on the PtSb2 surfaces to investigate their affinity with surfaces were performed considering different adsorption sites in order to find the most stable exothermic preferred site. In respect of the (100) surface, we noted that the bridging on Pt and Sb atoms by the collector involved the S atoms for all xanthates. Their adsorption energies showed that EX had strong affinity with the surface and the order was as: EX ≈ AX > nBX > nPX. In the case of the (110) surface the bridging on Pt atoms were PtSb2 Bulk PtSb2 (100), (110) and (111) surfaces O2, H2O, OH- and Xanthates adsorptions the most preferred sites for EX, nPX, nBX and AX. The order of adsorption energies was: nBX > nPX ≈ AX > EX. The (111) surface was observed to have the bridging on Sb2 and Sb3 atoms most exothermic for EX, nBX and AX, while the nPX showed the bridging on Pt1 and Sb3 atoms. The adsorption energies were found to have the nPX more stronger on the surface, with EX weaker and the order decreased as: nPX > nBX > AX > EX. This gave insights in the recovery of the minerals during flotation, that the use of EX or AX may float the platinum antimonide better based on the adsorption trends on the (100) surface, which is the most stable surface plane cleavage for platinum antimonide. The analysis of the electronic structures of the collector on the surface from density of states showed stability bonding of the collector on the surface, due to the EF falling deep into the pseudo gap for collector S atoms and surface Pt and Sb PDOS. The atomic charges computed indicated that the collectors behave as electron donors and acceptors to the Pt and Sb on the surface, respectively for the (100) surface. Interestingly for the (110) surface we observed that both surface Pt and Sb atoms lost charges, with a loss of charges on the collector S atoms. These observations suggested that the collectors S atoms offer their HOMO electrons to Pt and Sb atoms to form bond and simultaneously the Pt and Sb atoms donate their d-orbital and p-orbitals electrons to the LUMO of the collectors to form a back donation covalent bond, respectively. The (111) surface clearly showed that the surface Pt and Sb atoms lose charges to the collector S atoms, suggested a back donation covalent bonds.
Thesis (Ph.D.(Physics)) -- University of Limpopo, 2020
Keywords: exothermic adsorption; Atomic charges; Xanthates; Absorption cross sections; Xanthates